2020
DOI: 10.1080/21505594.2020.1814091
|View full text |Cite
|
Sign up to set email alerts
|

Canine parvovirus induces G1/S cell cycle arrest that involves EGFR Tyr1086 phosphorylation

Abstract: Canine parvovirus (CPV) has been used in cancer control as a drug delivery vehicle or anti-tumor reagent due to its multiple natural advantages. However, potential host cell cycle arrest induced by virus infection may impose a big challenge to CPV associated cancer control as it could prevent host cancer cells from undergoing cell lysis and foster them regain viability once the virotherapy was ceased. To explore CPV-induced cell cycle arrest and the underlying mechanism toward improved virotherapeutic design, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Viruses can control their infection and replication by regulating the G1/S and G2/M boundaries ( Miranda and Thompson, 2016 ; Qi et al, 2020 ). At present, CPV-related pathogenic molecular mechanisms are mainly focused on the effects of NS1 protein on apoptosis, cell cycle, and related signaling pathways ( Gupta et al, 2016 ; Lin et al, 2019 ; Dai et al, 2020 ). In addition, studies have shown that the cellular DNA damage response triggered by the invading single-stranded parvovirus can induce cell cycle arrest, thereby creating a favorable environment for viral replication ( Chen and Qiu, 2010 ; Lou et al, 2012 ; Xu et al, 2019 ; Zhang et al, 2019 ; Dai et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Viruses can control their infection and replication by regulating the G1/S and G2/M boundaries ( Miranda and Thompson, 2016 ; Qi et al, 2020 ). At present, CPV-related pathogenic molecular mechanisms are mainly focused on the effects of NS1 protein on apoptosis, cell cycle, and related signaling pathways ( Gupta et al, 2016 ; Lin et al, 2019 ; Dai et al, 2020 ). In addition, studies have shown that the cellular DNA damage response triggered by the invading single-stranded parvovirus can induce cell cycle arrest, thereby creating a favorable environment for viral replication ( Chen and Qiu, 2010 ; Lou et al, 2012 ; Xu et al, 2019 ; Zhang et al, 2019 ; Dai et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, CPV-related pathogenic molecular mechanisms are mainly focused on the effects of NS1 protein on apoptosis, cell cycle, and related signaling pathways ( Gupta et al, 2016 ; Lin et al, 2019 ; Dai et al, 2020 ). In addition, studies have shown that the cellular DNA damage response triggered by the invading single-stranded parvovirus can induce cell cycle arrest, thereby creating a favorable environment for viral replication ( Chen and Qiu, 2010 ; Lou et al, 2012 ; Xu et al, 2019 ; Zhang et al, 2019 ; Dai et al, 2020 ). While as an important component of the viral capsid, the CPV VP2 protein not only determines the host range of the virus ( Hueffer and Parrish, 2003 ), but also serves as a key protein in inducing the host immune defense mechanism ( Sarabandi and Pourtaghi, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inoculating cells with a 10-gradient sequentially diluted solutions of viral fluid at a step-size of 10 folds, and monitoring cells for 5 to 7 days until the occurrence of cytopathic effect (CPE) in 50% cells. TCID50 was calculated following previously recommended protocol 21 .…”
Section: Methodsmentioning
confidence: 99%
“…CPV causes DNA disruption and interferes with the cell cycle, generating time to increase viral progenies leading to pathological consequences of infection, causing cell death after cell cycle arrest (Figure4) (49). In the Norden Laboratory Feline Kidney cell line (NLFK) and the Canine Fibroma cell line (A72), CPV causes cell cycle arrest in the S phase(49,58). Cell cycle arrest and DDR signaling evidently have significant role in canine parvovirus infections as inhibition of DDR interferes with viral replication and lowers the production of progeny(59).…”
mentioning
confidence: 99%